Screening of Halophilic Lipase-Producing Bacteria and Characterization of Enzyme for Fish Sauce Quality Improvement - Werasit Kanlayakrit; Anan Boonpan (Agriculture and Natural Resources, 2007)
Twenty pure bacterial cultures isolated from Thai fish sauce were selected for lipase producing on Sehgal and Gibbons Complex (SGC)-Tween 80 agar containing 0-4 M NaCl. The results showed that isolate PB233 could produce the highest lipase activity. This isolate was identified based on morphological, physiological characteristics and compared 16S rRNA sequence to other bacteria. It was concluded that isolate PB233 belonged to Staphylococcus warneri. This strain could grow in 0-4 M NaCl but the best growth was observed at 0 M NaCl. Therefore, Staphylococcus warneri was classified as halotolerant bacteria. A halotolerant Staphylococcus warneri PB233 was cultured in mini jar fermenter using SGC medium containing 1% olive oil and 3 M NaCl. A typical pattern of lipase production showed that enzyme secretion was coupled to active cell multiplication and maximum activity was obtained at a stationary phase. The maximum production of lipase (90.12 U/ml) was observed at 48 hr. The lipase had optimum at pH 7.0 and at temperature of 40°C. It was stable between pH 7.0 and 9.0 and at temperatures between 30 and 40°C. This enzyme had marked halophilic enzyme properties and showed maximal activities in the presence of 2.5 M (15%) NaCl.